Understanding viewers’ purchase of intangible cultural heritage (ICH) products: a perspective of the Means-End Chain (MEC) framework - Bo Zhang; Yannan Zhang (Humanities & Social Sciences Communications)
Abstract The live streaming of intangible cultural heritage (ICH) has innovated the trading and marketing methods of ICH products, promoting the prosperity of the ICH market. However, there is still limited research on how the live streaming of ICH pushes viewers to consume ICH products, and the specific mechanism is still unclear. To this end, this study proposes a research model based on the Means-End Chain (MEC) framework to unpack the influence of parasocial interaction and vicarious learning on the viewers’ perceived value and purchase intention of ICH products, including the moderating effect of perceived enjoyment. 376 responses were obtained using a self-reported survey and analyzed employing structural equation modeling. The results revealed that (1) Both parasocial interaction and vicarious learning have a positive effect on perceived value; (2) Perceived value positively predicts purchase intention; (3) Perceived enjoyment negatively moderates the effects of parasocial interaction and vicarious learning on perceived value. This study provided a new perspective to study the viewers’ intention to purchase ICH products, enriching the relevant theories and practices of ICH.